Analysis of Arabidopsis thaliana root growth kinetics with high temporal and spatial resolution - Yazdanbakhsh, Nima (Oxford University Press, 2010)
BACKGROUND: Methods exist to quantify the distribution of growth rate over the root axis. However, non-destructive, high-throughput evaluations of total root elongation in controlled environments and the field are lacking in growth studies. A new imaging approach to analyse total root elongation is described. SCOPE: High pixel resolution of the images enables the study of growth in short time intervals and provides high temporal resolution. Using the method described, total root elongation rates are calculated from the displacement of the root tip. Although the absolute root elongation rate changes in response to growth conditions, this set-up enables root growth of Arabidopsis wild-type seedlings to be followed for more than 1 month after germination. The method provides an easy approach to decipher root extension rate and much simpler calculations compared with other methods that use segmental growth to address this question. CONCLUSIONS: The high temporal resolution allows small modifications of total root elongation growth to be revealed. Furthermore, with the options to investigate growth of various mutants in diverse growth conditions the present tool allows modulations in root growth kinetics due to different biotic and abiotic stimuli to be unravelled. Measurements performed on Arabidopsis thaliana wild-type (Col0) plants revealed rhythms superimposed on root elongation. Results obtained from the starchless mutant pgm, however, present a clearly modified pattern. As expected, deviation is strongest during the dark period.